Rising East Asia the quest for governance, prosperity, and security - Li, Jianbin (Thousand Oaks, California CQ Press, an imprint of SAGE Publications, Inc., 2021)
"Rising East Asia by Chien-pin Li helps readers understand the dynamic changes to China, Japan, and Korea since the end of World War II. Although the three countries have experienced stellar economic growth, there have also been shifts in political dynamics, social order, and security landscapes. To help people understand the past and present of the region, and develop well-informed opinions about its future, Li offers a book for East Asian Politics courses that reflects interdisciplinary collaboration-one that brings the scholarly debate in comparative politics and international relations to bear on the rich information and knowledge accumulated from East Asian studies. Each section is organized around the pursuit of three policy goals: economic prosperity, political governance, and national security. Whatever their position may be, the future of the region is likely to have major impacts on the rest of the world."--Provided by publisher.
Includes bibliographical references and index.
Keywords: East Asia -- Foreign relations -- 21st century